ANALISIS PERBANDINGAN RISK DAN RETURN SAHAM SYARIAH DAN KONVENSIONAL PADA JAKARTA ISLAMIC INDEX (JII30) DAN INDEKS LQ45 PERIODE TAHUN 2020-2022 - Abdul Khakim; Mustafidah, Wiwit (Jurnal Ekonomi Syariah Darussalam, 2023)
The purpose of this study is to find out the difference in the average Return and Risk of Islamic stocks on the Jakarta Islamic Index (JII) and conventional stocks on LQ45 in the period 2020 to 2022 from the website www.idx.co.id. The results of the descriptive analysis show that the returns on Islamic stocks are higher than conventional stocks (0.0095350 > 0.0046987 or 0.95% > 0.46%). Meanwhile, the risk level is higher for sharia stocks than conventional stocks, namely 0.1072991 > 0.1019323 or 10.72% > 10.19%. Based on the results of the different test using the Independent Sample t-test, it was found that the Equal Variance Assumed assumption can be identified as the Sig. (2-tailed) > ? value with a significance value of 0.737> 0.05, while the assumption of Equal Variances Assumed Return value Sig. (2-tailed) > ? value with a significance value of 0.607> 0.05. From these data it can be concluded that the results of the significance of risk and stock returns show a significance value that is greater than the significance level ? = 5% (0.05) so that it can be interpreted that there is no significant difference between the Return and Risk of Islamic stocks and conventional stocks.